Pengaruh Risiko Kerusakan Peralatan Terhadap Kepuasan Pelanggan Pada Usaha Rumahan Wirda Laundry - Nasution, Hilda Yuni Br; Rinardi, Madila; Pratama, Nayla Dinda; Sitanggang, Nina Nur Rizki; A, Arsyadona (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Customer satisfaction is very important for service industries such as laundry, especially small-scale or home-based ones. Equipment failure, especially major equipment such as washing machines and dryers, has the potential to reduce service quality because it affects the turnaround time and the final results received by customers, and can cause service delays, inconsistent results, and losses for the business. The purpose of this study was to investigate the impact of equipment failure risk on customer satisfaction in the Wirda Laundry home business. The extent to which equipment failure risk affects customer satisfaction is determined in this study. To ascertain the degree to which equipment failure risk influences customer happiness, this study employs a quantitative approach using a straightforward linear regression analysis method. Wirda Laundry customers who were randomly selected received a questionnaire to collect data. Customer satisfaction and equipment failure risk were shown to be significantly correlated negatively, with a Pearson correlation value of 0.357 and a significance level of p of 0.01. This means that the level of customer satisfaction reported is negatively correlated with the risk of equipment failure. The results showed that preventive measures, such as regular equipment care and maintenance, are essential to reduce the risk of damage and ensure optimal customer satisfaction. In an increasingly competitive market, this strategy can not only maintain good relationships with customers but also increase Wirda Laundry's competitiveness.Customersatisfactionisveryimportantforserviceindustries suchaslaundry,especiallysmall-scaleorhome-basedones.Equipment failure, especially major equipment such as washing machines and dryers,has the potential to reduce service quality because it affects the turnaround timeandthefinalresultsreceivedbycustomers,andcancauseservice delays,inconsistentresults,andlossesforthebusiness.Thepurposeof thisstudywastoinvestigatetheimpactofequipmentfailureriskon customer satisfaction in the Wirda Laundry home business. The extent towhichequipmentfailureriskaffectscustomersatisfactionisdeterminedin thisstudy.Toascertainthedegreetowhichequipmentfailurerisk influences customer happiness, this study employs a quantitative approach using a straightforward linearregressionanalysis method.Wirda Laundrycustomerswhowererandomlyselectedreceivedaquestionnaireto collect data.Customer satisfaction and equipment failure risk were shown to be significantly correlated negatively, with a Pearson correlation value of 0.357 and a significance level of p of 0.01. This means that the level of customer satisfaction reported is negatively correlated with the risk of equipment failure. The results showed that preventive measures, such as regular equipment care and maintenance, are essential to reduce the risk ofdamage and ensure optimal customer satisfaction. In an increasingly competitive market, this strategy can notonly maintain good relationships with customers but also increase Wirda Laundry's competitiveness.